Legal Certainty Deed of Sale and Purchase of Land and Building conducted by husband and wife after divorce based on Government Regulation No. 24 of 1997 on registration of land - Abdul Syukur; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To Know and analyze the Legal Certainty Deed of Sale and Purchase of Land and Building conducted by husband and wife after divorce based on Government Regulation No. 24 of 1997 on Land Registration. 2) To Know and analyze weaknesses Sale and Purchase Agreements Law of Land and Buildings performed by husband and wife after divorce based on Government Regulation No. 24 of 1997 on Land Registration. 3) To Menegetahui and analyze how solutions address the legal shortcomings Deed of Sale and Purchase of Land and Building conducted by husband and wife after divorce based on Government Regulation No. 24 of 1997 on Land Registration The data used in this study are primary data, secondary data and data tertiary that can support assessment,Based on the results of data analysis concluded that: 1) Rule of Law Deed of Sale and Purchase of Land and Building conducted by husband and wife after divorce based on Government Regulation No. 24 of 1997 on Land Registration declared legally valid if in accordance with the terms of buying and selling land and buildings in accordance with article 37 paragraph 1 of Government Regulation No. 24 of 1997 and proving that the right to land and building will be transferred transitioning right evidenced by a deed made by and before PPAT that the deed of sale which will then be used as the basis of registration of changes in land registration data. 2) deficiencies, legal certainty deed of sale of land and building is done by husband and wife after divorce are on how the process of making the PPAT deed, the signatories of the deed of sale both parties must be on the terms of buying and selling is done in the presence of public officials who authorized and paid in cash. 3) to overcome the solution weakness against legal certainty deed of sale of land and buildings before registering the land to the National Land Agency (BPN) requirements in the execution of the sale and purchase must be taken by both sides in this case the former husband and wife so that in the future no one one side of those demanding the validity of the deed of sale.Keywords: Rule of Law, Sale and Purchase Agreements, Land Registry